Repeat drug-coated balloon angioplasty for femoropopliteal lesions: 12-month results from a retrospective observational study - Takuya Haraguchi; Masanaga Tsujimoto; Yoshifumi Kashima; Katsuhiko Sato; Tsutomu Fujita (CVIR Endovascular, 2024)
Abstract Background The clinical implications of restenosis after drug-coated balloon (DCB) treatment remain unclear. We compared the clinical outcomes between DCB angioplasty for restenosis and de novo femoropopliteal artery lesions. This single-center retrospective study included 571 patients (737 limbs) who underwent either repeat (54 patients, 64 limbs) or de novo DCB (517 patients, 673 limbs) without bailout stenting. After propensity score matching, 49 matched pairs were analyzed. The primary endpoint was the 1-year primary patency, with secondary endpoints including the freedom from target lesion revascularization (TLR), major adverse limb events (MALE), and early restenosis. Predictors of restenosis were identified using multivariable Cox regression analysis. Results The repeat-DCB group displayed significantly lower rates of 1-year primary patency and freedom from TLR compared to those of the de novo-DCB group (50.1% vs. 77.4%, p = 0.029 and 54.9% vs. 83.6%, p = 0.0.44, respectively). No significant differences were observed in early restenosis or MALE (10.7% vs. 5.9%, p = 0.455 and 48.3% vs. 73.4%, p = 0.055, respectively). Restenosis after DCB angioplasty was associated with repeat DCB (hazard ratio [HR], 5.13; 95% confidence interval [CI], 1.43–18.4; p = 0.012) and small vessel size of < 4.5 mm (HR, 6.25; 95% CI, 1.17–33.4; p = 0.032). Furthermore, restenosis after repeat DCB angioplasty was associated with the Peripheral Artery Calcification Scoring System (PACSS) grade 4 (HR, 4.20; 95% CI, 1.08–16.3; p = 0.038), small vessel size of < 4.5 mm (HR, 9.44; 95% CI, 1.21–73.7; p = 0.032), and intravascular ultrasound (IVUS) use (HR, 0.05; 95% CI, 0.01–0.44; p = 0.007). Conclusions The 1-year primary patency rate following repeat DCB angioplasty for femoropopliteal lesions was notably lower than that of DCB treatment for de novo lesions. Repeat DCB strategy was associated with an increased risk of patency loss. Regarding repeat restenosis after DCB treatments, PACSS grade 4 calcification and small vessel diameter of < 4.5 mm were associated with an increased risk of restenosis, whereas IVUS use correlated with a decreased risk of restenosis.